Strengthening pharmaceutical care in nuclear medicine: the role of Drug-Related Problem (DRP) identification / Nurulfalahin Daud @ Ibrahim and Muhamad Faiz Othman - Daud @ Ibrahim, Nurulfalahin; Othman, Muhamad Faiz (Faculty of Pharmacy, 2025)
The identification and classification of drug related problem (DRP) are fundamental to delivering optimal pharmaceutical care. This critical step ensures the safe, effective, and economical use of medications, ultimately improving therapeutic outcomes. Numerous studies have demonstrated the benefits of DRP identification, including reduced morbidity and mortality, shorter hospital stay and lower treatment cost. These benefits align with the core goals of pharmaceutical care as defined by the American Public Health Association (APhA) that is optimise the patient’s health-related quality of life and to achieve positive clinical outcomes, within realistic economic parameters.